Influence of Benggang slope cracks on soil water regimes: Comparison of model simulation and time‐domain reflectometry. (4th October 2022) - Duan, Xiaoqian; Deng, Yusong; Liu, Changxin; He, Yangbo; Lin, Lirong; Chen, Jiazhou
Abstract: Cracks greatly influence the saturated hydraulic conductivity ( K s ) of soil and are one of the most important factors for increasing K s . Moreover, both cracks and K s influence soil water distribution. This study aimed to investigate the consistency of the effects of cracks and K s on the water distribution along slopes. K s was measured in three soil layers along two typical Benggang (a severe gully erosion landform) slopes using a double‐ring infiltrometer. The K s values show a gradual decrease with increasing distance from the gully head in the same soil layer, and this phenomenon is consistent with the distribution of cracks on the slope measured by the staining tracer method. This indicates that the distribution of cracks can be accurately predicted by measuring the spatial variation in K s . The VADOSE/W model was employed to simulate soil water configurations and yielded inaccurate simulation results, typically in the lower slope. In addition, the simulation results were greatly improved through the inclusion of effective cracks by adjusting the material properties, but not solely by adjusting the K s . Therefore, the influence of cracks on the water distribution is not well reflected by K s, and cracks must be incorporated into the relevant models. The soil water content in the topsoil of the lower slope near the headwall with more cracks was than that of the upper slope, implying that cracks likely accelerate the downward movement of water and increase leakage. This process increases the water content and pore water pressure in deeper soil layers, thereby eventually increasing the likelihood of soil erosion. The results of this study can improve our understanding of the triggers of Benggang erosion and provide guidance on the prevention and control of soil erosion risks in areas with granitic soil. Highlights: The influence of cracks on water distribution cannot be strongly reflected by K s . Cracks must be considered when analysing the soil water content in a simulation mode. The distribution of cracks influences the timing and frequency of Benggang erosion. Soil cracks distribution is important in soil risk remediation and control such as Benggang erosion.